(untitled) (Senderos, 2025)
Urban forests play a vital role in preserving biodiversity within urbanized areas, serving as refuges for local fauna and connecting fragmented habitats. Birds, in particular, act as bioindicators, offering valuable insights into ecosystem health and climate change monitoring. This study evaluated bird diversity on the campus of the National University of Formosa, analyzing its relationship with urban forests and contribution to biodiversity conservation. The area was divided into four quadrants, surveyed for three hours in the morning and afternoon, three times a week between August and October 2024. A total of 65 bird species were observed—12% of the 550 recorded in the province—belonging to 12 orders and 25 families. Notable sightings include Tringa solitaria (solitary sandpiper) and Myiodynastes maculatus (streaked flycatcher), rare in urban settings, detected at a 6.25% frequency. This study offers a unique opportunity to integrate academic research with local environmental conservation efforts.